A DISEQUILIBRIUM MODEL FOR LEI-DENOMINATED NON-GOVERNMENTAL CREDIT IN ROMANIA - Cristian-Florin Dănănău (SEA: Practical Application of Science, 2015)

(untitled)
We empirically investigate through an econometric approach the Romanian credit market, namely the lei-denominated part of it, and the factors that interact with it. The main goal is to assess whether a credit crunch ocurred in Romania during the economic crisis. To this end we employ the disequilibrium model framework, set up in economic literature some 40 years ago. Our investigation takes into consideration the main macroeconomic determinants of this market, that interact with demand and supply. Our approach has in view the macroeconomic variables such as output, interest rates and foreign currency credit. The demand and supply function are estimated through the maximization of a certain maximum likelihood function. The final conclusion is that, based on the estimated model, one cannot detect a credit crunch in the after-crisis period. This paper’s results show that empirically-constructed disequilibrium models can be used to properly describe the behavior of the lei-denominated credit market, by taking necessary precautions.